Management of Atopic Dermatitis in Adults in Saudi Arabia: Consensus Recommendations from the Dermatological Expert Group - Alakeel A; Al Sheikh A; Alraddadi AA; Alattas KM; Aldayel M; Alajlan MA; Al-Haddab M; Almohideb M; Fatani M; Hamadah IR; Alharithy R; Binamer Y; et al. (Dove Medical Press, 2022)
Abdullah Alakeel,1 Afaf Al Sheikh,2,3 Ali A Alraddadi,4- 6 Khalid Mohammed Alattas,7 Maha Aldayel,8 Mohammed Abdulaziz Alajlan,9 Mohammed Al-Haddab,1 Mohammad Almohideb,3,10 Mohamed Fatani,11 Issam R Hamadah,12 Ruaa Alharithy,13,14 Yousef Binamer,15,16 Kim Papp,17 Ahmed Elaraby18 1Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Division of Dermatology, Department of Medicine, King Abdulaziz Medical City, Riyadh, Saudi Arabia; 3Department of Dermatology, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 4Department of Dermatology, Ministry of National Guard-Health Affairs, Jeddah, Saudi Arabia; 5King Abdullah International Research Center, Jeddah, Saudi Arabia; 6King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 7King Fahad Central Hospital, Jazan, Saudi Arabia; 8Dammam Medical Complex, Dammam, Saudi Arabia; 9Dermatology Section MSD, King Fahad Medical City, Riyadh, Saudi Arabia; 10King Abdulaziz Medical City, Riyadh, Saudi Arabia; 11Hera General Hospital, Makkah, Saudi Arabia; 12King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia; 13Security Forces Hospital, Riyadh, Saudi Arabia; 14Princess Nourah University, Riyadh, Saudi Arabia; 15Department of Dermatology, King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia; 16Department of Dermatology, Alfaisal University, Riyadh, Saudi Arabia; 17Probity Medical Research Inc. and K. Papp Clinical Research Inc., Waterloo, ON, Canada; 18Bachelor of pharmacy, Cairo University, Giza, EgyptCorrespondence: Issam R Hamadah, Email ihamadah@kfshrc.edu.sa; issamhamadah@gmail.comBackground: Atopic dermatitis (AD) is a long-term, pruritic, recurrent, systemic, inflammatory skin disorder. In the Middle East region, the burden of AD is understudied, and there is a dearth of AD guideline documents for practitioners.Methods: An expert panel meeting, encompassing 12 dermatologists from the Kingdom of Saudi Arabia (KSA), was congregated to develop evidence- and experience-based consensus recommendations for AD management, especially in adults in KSA. They completed a questionnaire with seven clinical statements, and a consensus was defined when the responses of ≥ 75% of participants coincided.Results: The expert recommendations were as follows: American Association of Dermatology guidelines are to be followed for defining AD; Eczema Area and Severity Index or SCORing atopic dermatitis index may be used to quantify the disease severity; Dermatology Life Quality Index may be used to determine the impact of AD on patients' quality of life; Atopic Dermatitis Control Tool may be used to assess long-term disease control in AD patients; and the European guidelines are to be followed for the management of AD. In AD patients who are inadequately controlled with topical or systemic therapies, the preferred systemic agent for use either alone or in combination with topical treatments is dupilumab, cyclosporine, methotrexate, phototherapy, or other available systemic treatments that may include mycophenolate mofetil or oral corticosteroids.Conclusion: These expert recommendations assist physicians by providing a reference framework for optimal care of adult AD patients.Keywords: atopic dermatitis, Dermatology Life Quality Index, Eczema Area and Severity Index, SCORing atopic dermatitis